Development of a Mini Calculator Application for Processing Odd and Even Numbers Using Dev-C++ - Sari, Indah Rahma; Anggraini, Amelia; S, Asiawatie; Abdullah, Zet; Sari, Novita; Putri, Hijrah Hasanah (Pascal: Journal of Computer Science and Informatics, 2025)
A mini calculator is a simple application designed to perform basic arithmetic operations such as addition, subtraction, multiplication, and division. This mini calculator program was developed using Dev-C++ with the primary goal of providing a practical solution for users to perform numeric calculations interactively. During the development process, several key issues were identified, including difficulties in accessing the calculator after the initial calculation, input errors, and the program’s inability to handle repeated operations without restarting the application. The development method utilized in this application was procedural programming, incorporating the use of the do-while loop structure. This approach enables the calculator to continuously request input and perform computations based on user choices without the need to close or restart the program. The do-while loop ensures that users can carry out multiple operations in succession until they choose to exit. To address the aforementioned issues, several solutions were implemented. These include input validation mechanisms to handle errors such as division by zero or invalid inputs, as well as an interactive menu system that facilitates operation selection. Moreover, error handling features were incorporated to provide users with clear messages in the event of incorrect operations. Separate functions were implemented for each mathematical operation to enhance code modularity and maintainability. The development stages of this application involved the following steps: (1) designing the algorithm and calculator menu structure; (2) implementing individual functions for each arithmetic operation; (3) applying the do-while loop to control the program’s iterative flow; (4) conducting testing and debugging to ensure proper functionality; and (5) refining the user interface and error messages to enhance user experience. In conclusion, the use of the do-while loop as a program repetition method has proven to be effective in maintaining the calculator application’s interactivity without requiring a restart. The program provides an efficient and user-friendly solution for repeated calculations through a simple and responsive interface.